2020
DOI: 10.3390/ijms21207756
|View full text |Cite
|
Sign up to set email alerts
|

Antiphotoaging Effect of 3,5-Dicaffeoyl-epi-quinic Acid against UVA-Induced Skin Damage by Protecting Human Dermal Fibroblasts In Vitro

Abstract: Cutaneous aging is divided into intrinsic and exogenous aging correspondingly contributing to the complex biological phenomenon in skin. Intrinsic aging is also termed chronological aging, which is the accumulation of inevitable changes over time and is largely genetically determined. Superimposed on this intrinsic process, exogenous aging is associated with environmental exposure, mainly to ultraviolet (UV) radiation and more commonly termed as photoaging. UV-induced skin aging induces increased expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…For example, one in vitro study on 3,5- O -dicaffeoylquinic acid isolated from Artemisia lavandulaefolia , found that it exhibited anti-rosacea effects [ 65 ]. Additionally, 3,5- O -dicaffeoylquinic acid demonstrated an anti-photoaging effect against skin damage induced by radiation in the UVA region (400–315 nm) and protected human dermal fibroblasts in vitro [ 66 ]. As 3,5- O -dicaffeoylquinic acid was the most prevalent compound in both extracts, this confirmed the potential of the prepared extracts for use in cosmetics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one in vitro study on 3,5- O -dicaffeoylquinic acid isolated from Artemisia lavandulaefolia , found that it exhibited anti-rosacea effects [ 65 ]. Additionally, 3,5- O -dicaffeoylquinic acid demonstrated an anti-photoaging effect against skin damage induced by radiation in the UVA region (400–315 nm) and protected human dermal fibroblasts in vitro [ 66 ]. As 3,5- O -dicaffeoylquinic acid was the most prevalent compound in both extracts, this confirmed the potential of the prepared extracts for use in cosmetics.…”
Section: Resultsmentioning
confidence: 99%
“…However, as the essential oil components are highly lipophilic, it is not likely that their concentration in the CD-aqueous extracts would be sufficient to be solely responsible for the observed effects. It is interesting to note that 3,5- O -dicaffeoylquinic acid decreases interstitial collagenase production and increases type I collagen production in UVA-damaged human dermal fibroblasts [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antiphotoaging activity showed derivates of detected quinic acid-3,5-Dicaffeoyl-epi-quinic acid. This effect was tested against skin damage induced by UVA and UVB radiation in human fibroblasts [ 85 , 86 ]. Published studies suggested that inositol may be effective in patients with moderate acne [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skin collagen is responsible for ECM structure and contributes to skin elasticity [23]. Therefore, we performed ELISA and western blotting to investigate the effects of Q-3-GR on procollagen type I production and protein expression upon UVA-induced photoaging.…”
Section: Effects Of Q-3-gr On Procollagen Type I Expression In Uvairr...mentioning
confidence: 99%